CHARACTERISTICS OF CRY1AB PROTEIN FROM BIOINSECTICIDES AND INSECT RESISTANT GM CROPS - Żmijewska, Ewelina; Linkiewicz, Anna; Żurawska-Zajfert, Magdalena; Grelewska-Nowotko, Katarzyna; Sowa, Sławomir; Zimny, Janusz (Plant Breeding and Seed Science, 2016)
Biological insecticides are an effective method used in plant protection. One of the most widely used active substances in biological insecticides is Cry1Ab protein, which is toxic for lepidopteran insects. This protein is produced during bacterial sporulation by Bacillus thuringiensis. Other sources of Cry1Ab protein are genetically modified plants (GM) with expression of cry1Ab gene. Cry1Ab protein in both bioinsecticides and GM plants is present in the form of protoxin, which requires activation by enzymatic treatment in the gut of susceptible insects. So far, Cry1Ab mode of action is not fully understood, but there are 3 main concepts describing it. Two of them assume that a toxic protein after binding to receptors in the insect gut penetrates into the cells, causing pore formation in the gut, which leads to the death of the sensitive insect. In the third model Cry1Ab toxic action is a result of toxin-induced chemical processes initiating a cell death pathway. This work describes the structure and mode of action of Cry1Ab protein, present in biological insecticides and genetically modified plants.